Hypomelanosis of Ito - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The neurological complications in 34 Spanish children with hypomelanosis of Ito are described from the Paediatric Neurology Service, Hospital Infantil La Paz, and La Universidad Autonoma, Madrid, Spain.